Two newly recorded genera Malayepipona Giordani Soika and Megaodynerus Gusenleitner, with eight new species from China (Hymenoptera, Vespidae, Eumeninae) - Chen, Yue Bai, Bin; Chen, Bin; Li, Ting-Jing (Zootaxa, 2021)
In this paper, the genera Malayepipona Giordani Soika and Megaodynerus Gusenleitner are newly recorded from China. Seven new species of Malayepipona and one new species of Megaodynerus are described and illustrated: namely Malayepipona brunnea Bai, Chen & Li, sp. nov., M. flaviclypeata Bai, Chen & Li, sp. nov., M. lamellata Bai, Chen & Li, sp. nov., M. maculosa Bai, Chen & Li, sp. nov., M. nigricans Bai, Chen & Li, sp. nov., M. sparsipuncta Bai, Chen & Li, sp. nov., M. triangula Bai, Chen & Li, sp. nov. and Megaodynerus bimaculus Bai, Chen & Li, sp. nov.. The species Malayepipona clypeata Nguyen & Carpenter, 2013 is also newly recorded from China. A key to known species of Malayepipona is updated.